Capitalizing on social interactions : facebook use and political participation amongst Singapore's youths. - Leow, Kai Ling. (2009)
Social Networking Sites (SNSs) have attracted much scholarly interest due to their ability to facilitate social interactions - the basis for the formation of social capital (Putnam, 2000). Using a nationally-representative sample of Singaporean youths, this study sought to explore how the use of the popular SNS, Facebook, relates to online social capital and political participation. Consistent with previous studies (e.g., Ellison, Steinfield, & Lampe, 2007), intensity of Facebook use was found to be positively associated with online bonding and online bridging social capital. Facebook use was also positively associated with political participation potential. The relationship between online bridging social capital and the likelihood of political participation was found to be only marginally significant. Measures of television and newspaper use were found to be associated with political participation potential, suggesting that both traditional and new forms of media are important in invigorating political and civic life today.